Pengaruh Model Pembelajaran Kooperatif Tipe STAD, Konvensional Dan Motivasi Belajar Terhadap Hasil Belajar Bolavoli Siswa Sma N 9 Kota Jambi - OKTADINATA, ALEK (Cerdas Sifa Pendidikan, 2015)
Based on observations, the research found that student SMAN 9 Jambi were not able to do basic vollyball techniques correctly. Furthermore, the method given by the teacher was classic and individual. The aim of this research to find out the infuence of the STAD type cooperative learning methods, conventional learning methods and the level of student motivation toward volleyball learning achievement.The study was quasi-experimental, data had analyzed by using variance two-lane (ANAVA 2x2) and tukey test.while the samples in this study were 52 students The results of data analysis show that: (1) there it’s a difference in academic achievement volleyball between STAD type of cooperative groups volleyball and conventional type was declined, (2) there is a difference between learning achievement volleyball groups that have high level motivation and low level motivation, (3) there interaction between learning methods and the level of learning motivation in improving learningachievementvolleyball. Kata Kunci : Model Kooperatif, Tipe STAD, Model Konvensional, Motivasi Belajar, Hasil Belajar Bolavoli